Galactic evolution of sulphur as traced by globular clusters - Kacharov, Nikolay; Koch-Hansen, Andreas; Caffau, Elisabetta; Sbordone, Luca (Astronomy and astrophysics, 2015)
Sulphur is an important volatile α element, but its role in the Galactic chemical evolution is still uncertain, and more observations constraining the sulphur abundance in stellar photospheres are required.Aims. We derive the sulphur abundances in red giant branch (RGB) stars in three Galactic halo globular clusters (GC) that cover a wide metallicity range (−2.3 < [Fe/H] < −1.2): M 4 (NGC 6121), M 22 (NGC 6656), and M 30 (NGC 7099). The halo field stars show a large scatter in the [S/Fe] ratio in this metallicity span, which is inconsistent with canonical chemical evolution models. To date, very few measurements of [S/Fe] exist for stars in GCs, which are good tracers of the chemical enrichment of their environment. However, some light and α elements show star-to-star variations within individual GCs, and it is as yet unclear whether the α element sulphur also varies between GC stars.Methods. We used the infrared spectrograph CRIRES to obtain high-resolution (R ~ 50 000), high signal-to-noise (S/N ~ 200 per px) spectra in the region of the S I multiplet 3 at 1045 nm for 15 GC stars selected from the literature (six stars in M 4,six stars in M 22, and three stars in M 30). Multiplet 3 is better suited for S abundance derivation than the more commonly used lines of multiplet 1 at 920 nm, since its lines are not blended by telluric absorption or other stellar features at low metallicity.Results. We used spectral synthesis to derive the [S/Fe] ratio of the stars assuming local thermodynamic equilibrium (LTE). We find mean [S/Fe]LTE = 0.58 ± 0.01 ± 0.20 dex (statistical and systematic error) for M 4, [S/Fe]LTE = 0.57 ± 0.01 ± 0.19 dex for M 22, and [S/Fe]LTE = 0.55 ± 0.02 ± 0.16 dex for M 30. The negative NLTE corrections are estimated to be in the order of the systematic uncertainties. We do not detect star-to-star variations of the S abundance in any of the observed GCs, with the possible exception of two individual stars, one in M 22 and one in M 30, which appear to be highly enriched in S.Conclusions. With the tentative exception of two stars with measured high S abundances, we conclude that sulphur behaves like a typical α element in the studied Galactic GCs, showing enhanced abundances with respect to the solar value at metallicities below [Fe/H]−1.0 dex without a considerable spread.
Gesehen am 17.06.2020